Laminate
Patent Information
- Application Number
- JP2023127898
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0010】 本発明によれば、機械的特性、制振特性、透明性、耐衝撃性に優れた積層体を提供することができる。 本発明の積層体は、スマートフォン、タブレットPC、ノートPC等のディスプレイ部材、ガラス中間膜として好適に利用することができる。
Smart Images

Figure 2025023604000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate having excellent mechanical properties, vibration-damping properties, transparency and impact resistance. [Background technology]
[0002] In many products, from automobiles, industrial products, daily necessities, to office equipment, vibration-absorbing materials made of resin compositions are often used in places where vibration occurs. These vibration-absorbing materials are usually required to have high mechanical properties and vibration-damping properties. In order to improve the mechanical properties and vibration-damping properties, it is known to fill the resin composition with inorganic fillers such as talc and mica.
[0003] For example, Patent Document 1 discloses a vibration-damping material containing a polyester resin and 30% by mass or more of mica flakes.
[0004] In recent years, office automation equipment that uses vibration-damping materials, such as liquid crystal displays and organic electroluminescence displays, is required to have transparency and impact resistance in addition to mechanical properties and vibration-damping properties.
[0005] For example, Patent Document 2 discloses a glass panel in which a resin film is laminated on at least one surface of a non-strengthened glass substrate.
[0006] However, the vibration-damping material of Patent Document 1 has a problem in that the transparency is impaired due to the influence of the large amount of inorganic filler contained therein, and the glass panel of Patent Document 2 has a problem in that the improvement in impact resistance is insufficient. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2008-189854 A [Patent Document 2] JP 2015-093401 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention is intended to solve the above problems, and has an object to provide a laminate having excellent mechanical properties, vibration-damping properties, transparency and impact resistance. [Means for solving the problem]
[0009] As a result of extensive research aimed at solving such problems, the inventors have discovered that the above object can be achieved by blending a specific amount of silica particles having a specific average particle size with a polyacrylate resin, and have thus arrived at the present invention. That is, the gist of the present invention is as follows. (1) A laminate in which a resin composition containing a polyacrylate resin and silica particles is laminated on at least one surface of a transparent substrate, the polyacrylate resin being at least a compound represented by the following general formula (1): [ka] [In formula (1), R 0 represents a hydrogen atom, a methyl group, or an ethyl group; R 1 represents a hydrogen atom or a methyl group; and n represents an integer of 1 to 9.] as a monomer unit, the content of the silica particles being 15 to 50 volume % of the entire resin composition, and the average particle diameter of the silica particles being less than 150 nm. (2)R 0 The laminate according to (1), wherein (3) The laminate according to (1) or (2), wherein the resin composition has a tensile breaking stress of 4.0 MPa or more. (4) The laminate according to (1) or (2), wherein the resin composition has a tensile breaking strain of 350% or more. (5) The laminate according to (1) or (2), wherein the loss factor of an unconstrained composite beam determined using a 1 mm-thick sheet made of the resin composition by the central excitation method based on JIS K 7391 is 0.040 or more. (6) The laminate according to (1) or (2), wherein the transmittance of visible light having a wavelength of 480 nm is measured using a 1 mm-thick sheet made of the resin composition, and is 70% or higher. (7) The laminate according to (1) or (2), wherein the 50% breaking height of the laminate is 300 mm or more. Effect of the Invention
[0010] According to the present invention, it is possible to provide a laminate having excellent mechanical properties, vibration-damping properties, transparency, and impact resistance. The laminate of the present invention can be suitably used as a display member for smartphones, tablet PCs, notebook PCs, and the like, and as a glass interlayer film. [Brief description of the drawings]
[0011] [Figure 1] Stress / strain curve of the resin composition obtained in Example 1 [Diagram 2] 4 is a stress / strain curve of the resin composition obtained in Comparative Example 1. [Diagram 3] 4 is a stress / strain curve of the resin composition obtained in Comparative Example 2. [Figure 4] 4 is a transmission spectrum of the resin composition obtained in Example 1. [Diagram 5] 4 is a transmission spectrum of the resin composition obtained in Comparative Example 1. [Figure 6] 4 is a transmission spectrum of the resin composition obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The laminate of the present invention is obtained by laminating a resin composition, which is a polyacrylate resin containing silica particles, on at least one surface of a transparent substrate.
[0013] The polyacrylate resin constituting the resin composition used in the present invention must contain, as a monomer unit, an acrylate monomer (A) represented by the following general formula (1). [ka]
[0014] In formula (1), R 0 R represents a hydrogen atom, a methyl group, or an ethyl group, preferably a hydrogen atom or a methyl group, more preferably a methyl group. 1 represents a hydrogen atom or a methyl group, and preferably a methyl group. n represents an integer of 1 to 9, preferably 1 to 5, more preferably 1 to 3, even more preferably 1 or 2, and most preferably 1.
[0015] The acrylate monomer (A) represented by the above general formula (1) can be converted into an acrylate resin by thermal polymerization or photopolymerization.
[0016] Specific examples of the acrylate monomer represented by general formula (1) include, for example, 2-methoxyethyl acrylate, 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, triethylene glycol monomethyl ether acrylate, triethylene glycol monomethyl ether methacrylate, polyethylene glycol monomethyl ether methacrylate (number average molecular weight 300), and polyethylene glycol monomethyl ether methacrylate (number average molecular weight 1100). From the viewpoint of improving the dispersibility of silica particles and the mechanical properties of the resulting resin composition, preferably, 2-methoxyethyl acrylate, 2-methoxyethyl methacrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, triethylene glycol monomethyl ether acrylate, triethylene glycol monomethyl ether methacrylate, more preferably, 2-methoxyethyl acrylate, diethylene glycol monomethyl ether acrylate, diethylene glycol monomethyl ether methacrylate, triethylene glycol monomethyl ether methacrylate, even more preferably, 2-methoxyethyl acrylate, diethylene glycol monomethyl ether methacrylate, and most preferably, diethylene glycol monomethyl ether methacrylate. The acrylate monomer represented by the general formula (1) may be used alone or in combination as long as it does not impair the effects of the present invention.
[0017] The polyacrylate resin may contain a difunctional or higher acrylate monomer as a crosslinking agent as a monomer unit. For example, the difunctional acrylate monomer may be ethylene glycol diacrylate, EO modified bisphenol A diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, trimethylolpropane diacrylate, polyethylene glycol diacrylate (polyethylene glycol chain molecular weight 100 to 10000), the trifunctional acrylate monomer may be trimethylolpropane triacrylate, pentaerythritol triacrylate, and the tetrafunctional or higher acrylate monomer may be pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, tripentaerythritol octaacrylate, tetrapentaerythritol decaacrylate, or pentapentaerythritol dodecaacrylate. In view of the dispersibility of silica particles and the physical properties of the resulting resin composition, a bifunctional acrylate monomer is preferred, preferably ethylene glycol diacrylate, 1,4-butanediol diacrylate, or diethylene glycol diacrylate, more preferably diethylene glycol diacrylate. The bifunctional or higher acrylates may be used alone or in combination as long as they do not impair the effects of the present invention.
[0018] In the above general formula (1), R 1 When an acrylate monomer in which is a hydrogen atom is used, the resulting acrylate resin has a glass transition point significantly below zero degrees and is highly viscous, making it difficult to handle. For this reason, it is preferable to use the above-mentioned di- or higher-functional acrylate monomer as the crosslinking agent.
[0019] The difunctional or higher acrylate monomer may be contained in the resin composition in an amount of less than 5 mol%, preferably less than 2 mol%, more preferably less than 1 mol%, and even more preferably less than 0.6 mol%, based on 100 mol% of all monomer units. If the difunctional or higher acrylate is 5 mol% or more, the tensile elongation at break is significantly reduced.
[0020] The polyacrylate resin may contain a silane coupling agent represented by the following general formula (2) as a monomer unit. [ka]
[0021] In formula (2), R 2 R represents a hydrogen atom or a methyl group, preferably a methyl group. 3 R represents a methoxy or ethoxy group, preferably a methoxy group. 4 represents a methyl group, a methoxy group or an ethoxy group, preferably a methyl group or a methoxy group.
[0022] Specific examples of the silane coupling agent represented by general formula (2) include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane. From the viewpoint of improving mechanical properties, 3-methacryloxypropylmethyldimethoxysilane or 3-methacryloxypropyltrimethoxysilane is preferred, and 3-methacryloxypropyltrimethoxysilane is more preferred. The silane coupling agent represented by general formula (2) may be used alone or in combination as long as it does not impair the effects of the present invention.
[0023] When the silane coupling agent is contained, the silane coupling agent is contained in an amount in the resin composition such that the surface coverage ratio of the silane coupling agent to the silica particles is in the range of 0.005 to 0.080, preferably 0.006 to 0.076, more preferably 0.007 to 0.080, and even more preferably 0.010 to 0.075.
[0024] Here, the surface coverage ratio is a value obtained by the following formula. [Surface coverage ratio] = [Amount of silane coupling agent contained in resin composition (g)] × [Minimum coverage area of silane coupling agent (m 2 / g)]÷[surface area of silica particles contained in the resin composition (m 2 )
[0025] "Minimum coverage area of silane coupling agent (m 2 "(O) / g" refers to the area that the silane coupling agent covers on the surface of a material such as silica when 1 g of the silane coupling agent reacts with or is adsorbed on the surface of the material. Usually, the minimum coverage area of each silane coupling agent can be calculated as follows. That is, Si(O) obtained by hydrolysis of trialkoxysilane is 3 Assuming that the model consists of one spherical Si atom with a radius of 2.10 Å, three spherical O atoms with a radius of 1.52 Å, a Si-O bond distance of 1.51 Å, and a tetrahedral angle of 109.5°, and further assuming that all three O atoms in the model react with the silanol groups on the silica surface, calculate the minimum circular area that can be covered by the three O atoms. As a result, the coverage area per molecule is 1.3 × 10 -19 m 2 / numerator, with Avogadro's constant 6.0 × 10 23 Multiplying by molecules / mole converts to per mole: 7.8 x 10 4 m 2 The minimum coverage area of each coupling agent is the value obtained by dividing the coverage area per mole by the molecular weight of each silane coupling agent.
[0026] Commercially available silane coupling agents have their characteristic values indicated and described, and in the present invention, the values indicated and described by the distributor may be used.
[0027] In addition, the surface area of silica particles (m 2 ) is the sum of the surface area (m2) of silica particles calculated from the average particle size. 2 ) × Amount of silica particles added (g) ÷ Density of silica particles (g / cm 3 ) / "Volume of silica particles calculated from the average particle size (m 3 ) is the value obtained by calculating
[0028] The polyacrylate resin may be combined with a different acrylate monomer in addition to the acrylate monomer (A) represented by general formula (1), and may contain a different silane coupling agent in addition to the silane coupling agent (B) represented by general formula (2), as long as the effects of the present invention are not impaired.
[0029] The silica particles constituting the resin composition used in the present invention are an important component from the viewpoint of improving the mechanical properties of the resin composition.
[0030] The shape of the silica particles is not particularly limited as long as it does not impair the effects of the present invention, but is preferably "spherical" from the viewpoint of transparency. In the present invention, "spherical" refers to a true sphere, an approximately sphere, or a spheroid, excluding rod-like and plate-like ones, and may have an uneven surface. "Spherical silica particles" are silica particles having such a "spherical" shape.
[0031] As the spherical silica particles, known ones such as powdered spherical silica particles and colloidal silica (silica sol) can be used, and various known ones having different average particle sizes are known and commercially available.
[0032] The silica particles must have an average particle size of 150 nm or less, preferably 140 nm or less, more preferably 130 nm or less, and even more preferably 120 nm or less. In the present invention, the average particle size is represented by a mode diameter measured by a centrifugal sedimentation type particle size distribution measuring device.
[0033] When a substance having a periodic structure such as a crystal is irradiated with light of a certain wavelength, interference of scattered light occurs due to the relationship between the optical path difference corresponding to the interval of the periodic structure and the angle of incidence of light and the wavelength of light under the Bragg condition shown in the relational expression 2dsinθ=nλ (d: interval between crystal planes, θ: angle between the crystal planes and the light, λ: wavelength of light, n: natural number). At a certain volume fraction or more, spherical silica particles form a colloidal crystal structure in which the particles are arranged periodically, and the center-to-center distance between adjacent spherical silica particles is d (interval between crystal planes) in the above relational expression. Since the wavelength at the short wavelength end of visible light is about 380 nm, if the center-to-center distance of spherical silica particles is shorter than half of this wavelength, the interference of scattered light will be at a shorter wavelength (ultraviolet region) than the visible light region, and structural coloring due to interference light will not occur. In a resin composition, when adjacent spherical silica particles are in contact with each other, the resin composition behaves as a solid with no flexibility, so the surface distance between the spherical silica particles must be at least 10 to 20 nm or more. In other words, in order to make the interference wavelength of scattered light shorter than the visible light region and to avoid coloration due to structural coloring and scattering of visible light, it is necessary for the spherical silica particles of the present invention to have an average particle size of less than 150 nm, thereby obtaining a resin composition with excellent transparency.
[0034] The content of the silica particles is required to be 15 to 50% by volume of the entire resin composition, preferably 15 to 45% by volume, more preferably 18 to 45% by volume, and even more preferably 34 to 44% by volume. The lower the content of the silica particles, the smaller the reinforcing effect of the polymer material due to the silica particle filling, and the inferior tensile stress at break and tensile strain at break are, which is not preferable. If the content of the granular silica particles is too high, it becomes difficult to uniformly disperse the silica particles in the acrylate monomer.
[0035] The volume percent (V(%)) of the resin composition, which indicates the content of silica particles in the present invention, is Density of the resin composition (d(g / m 3 ) and the weight retention rate (%) calculated from the weight (m(g)) residual after heating at 500°C for 1 hour, according to the following formula: V(%)=[density of resin composition (g / cm 3 )] × [Weight retention after heating at 500°C for 1 hour (%)] ÷ [Density of spherical silica particles (2.2 g / cm 3 )]
[0036] The resin composition used in the present invention can be obtained by polymerizing a dispersion containing an acrylate monomer (A) represented by general formula (1) and silica particles.
[0037] As the polymerization method, thermal polymerization using a thermal polymerization initiator, photopolymerization using a photopolymerization initiator accompanied by irradiation with active energy rays such as ultraviolet rays, etc. can be used, and other polymerization methods may also be used as long as they do not impair the effects of the present invention.
[0038] The thermal polymerization initiator is not particularly limited in structure as long as it generates radicals by heating and is used to initiate polymerization of the polymerizable functional group in the resin composition. For example, 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobis[2-(2-imidazolin-2-yl)propane], Benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxy 2-ethylhexanoate, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, diacetyl peroxide are listed, and 2,2'-azoisobutyronitrile (AIBN) is preferred in terms of reactivity. The amount of the thermal polymerization initiator added is 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and 7 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by weight of the acrylic monomer component. These thermal polymerization initiators may be used alone or in combination of two or more kinds.
[0039] The photopolymerization initiator is not particularly limited in structure as long as it is used to generate radicals by ultraviolet irradiation and initiate polymerization of the polymerizable functional group in the resin composition. As the photopolymerization initiator, it is preferable to use an initiator having a light absorption wavelength of 360 nm to 470 nm, and examples thereof include acylphosphine oxide-based, α-aminoacetophenone-based, benzophenone-based, camphorquinone-based and thioxanthone-based initiators. By using these initiators, polymerization proceeds efficiently to the inside of the resin composition, improving mechanical properties and reducing the amount of residual components such as initiators and monomers.Examples of photopolymerization initiators include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, ethyl (2,4,6-trimethylbenzoyl) phenylphosphine oxide, bis (2,4,6-trimethylbenzoyl) phenylphosphine oxide, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, oligo (2-hydroxy-2-methyl-1- (4- (1-methylvinyl) phenyl) propanone), 2-benzyl-2-dimethylamino-1- (4-morpholinophenyl) -butanone-1 ,2-Dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, 2-[4-(methylthiobenzoyl)]-2-(4-morpholinyl)propane, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 1-hydroxycyclohexyl phenyl ketone, [4-[4-methylphenyl]thio]phenyl]phenylmethanone, ethyl 4-(dimethylamino)benzoate, 1-[4-(2 -hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 4,4'-bis-(dimethylamino)benzophenone, 4,4'-diethylaminobenzophenone, 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-[(4-methylphenyl)sulfonyl]propan-1-one, (methylimino)diethane-2,1-diyl(4-dimethylamibenzoate), lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate, bis(4-methoxybenzo In view of reactivity, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate, and bis(4-methoxybenzoyl)diethylgermanium are preferred, and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide is more preferred.The amount of the photopolymerization initiator added is 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and 7 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, relative to 100 parts by weight of the acrylic monomer component. These photopolymerization initiators may be used alone or in combination of two or more kinds.
[0040] In addition, a chain transfer agent may be used in the polymerization reaction. Examples of the chain transfer agent include mercaptocarboxylic acids such as mercaptoacetic acid and 3-mercaptopropionic acid; mercaptocarboxylic acid esters such as methyl mercaptoacetate, methyl 3-mercaptopropionate, 2-ethylhexyl 3-mercaptopropionate, n-octyl 3-mercaptopropionate, methoxybutyl 3-mercaptopropionate, stearyl 3-mercaptopropionate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), and dipentaerythritol hexakis(3-mercaptopropionate); ethyl mercaptan, t-butyl mercaptan, n-dodecyl mercaptan, and the like. Examples of the chain transfer agent include alkyl mercaptans such as mercaptan and 1,2-dimercaptoethane; mercaptoalcohols such as 2-mercaptoethanol and 4-mercapto-1-butanol; aromatic mercaptans such as benzenethiol, m-toluenethiol, p-toluenethiol, and 2-naphthalenethiol; mercaptoisocyanurates such as tris[(3-mercaptopropionyloxy)-ethyl]isocyanurate; disulfides such as 2-hydroxyethyl disulfide and tetraethyl thiuram disulfide; dithiocarbamates such as benzyl diethyl dithiocarbamate; monomer dimers such as α-methylstyrene dimer; and alkyl halides such as carbon tetrabromide. The amount of the chain transfer agent to be added is 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and 7 parts by mass or less, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by weight of the acrylic monomer component. These may be used alone or in combination of two or more.
[0041] When using powdered silica particles as the silica particles, it is preferable to first disperse the silica particles in the acrylate monomer (A). The method of dispersing the silica particles in the acrylate monomer (A) is not particularly limited as long as it does not impair the effects of the present invention, but the method of ultrasonic treatment is preferable because of its high dispersion effect.
[0042] When colloidal silica (silica sol) is used as silica particles, it is preferable to use the organic solvent mixed with the acrylic monomer component, for example, alcohols, ketones, esters, glycol ethers.From the viewpoint of ease of solvent removal, it is preferable to use alcohol-based organic solvents such as methanol, ethanol, isopropyl alcohol, butyl alcohol, n-propyl alcohol, and ketone-based organic solvents such as methyl ethyl ketone and methyl isobutyl ketone, and specifically, it is preferable to use colloidal silica (silica sol) dispersed in methanol, isopropyl alcohol, or methyl ethyl ketone.
[0043] A preferred method for producing the laminate of the present invention is to prepare a dispersion liquid by mixing and dispersing a predetermined amount of silica particles in an acrylate monomer (A) represented by general formula (1), and then mixing and dispersing a polymerization initiator, other acrylic monomers, and desired additives in the dispersion liquid as necessary, and then coating the obtained dispersion liquid on a release film and polymerizing it, and then laminating the resin composition on the film with a transparent substrate, or coating the dispersion liquid on a transparent substrate to a desired thickness and polymerizing it. Examples of the desired additives include plasticizers, surfactants, dispersants, antioxidants, ultraviolet absorbers, fluorescent agents, crosslinking agents, organic solvents, etc., and may be added according to the purpose within a range that does not impair the effects of the present invention.
[0044] The resin composition used in the laminate of the present invention has a thickness in the range of 5 to 300 μm, preferably 10 to 200 μm, more preferably 20 to 150 μm, and further preferably 20 to 100 μm. If the thickness of the resin composition is greater than 300 μm, the mass of the laminate becomes heavy, and the handling property during the manufacturing process may be poor. If the thickness of the resin composition is less than 5 μm, the effect of improving impact resistance may be poor.
[0045] The transparent substrate used in the laminate of the present invention has a thickness in the range of 0.02 to 1 mm, and the material is not particularly limited, but examples thereof include polymer substrates such as polyester, polyamide, polyimide, and cycloolefin polymer, and glass substrates. From the viewpoint of improving impact resistance, it is preferable to use a glass substrate.
[0046] The glass substrate may be a plate-shaped one, and the material is not particularly limited, but examples thereof include soda-lime glass, borate glass, aluminosilicate glass, and quartz glass. In addition, the glass may be classified according to the alkali component into non-alkali glass and low-alkali glass. The alkali metal component (e.g., Na) of the glass may be a metal oxide, and the like. 2 OK 2 O, Li 2 The content of O) is preferably 15% by mass or less, and more preferably 10% by mass or less. The thickness of the glass substrate is preferably 0.02 to 1 mm, more preferably 0.03 to 0.7 mm, and even more preferably 0.05 to 0.5 mm. If the glass substrate is too thick, it may have poor flexibility, and if it is too thin, it may have insufficient strength and be easily broken.
[0047] The method for forming the glass substrate is not particularly limited, and for example, a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon is melted at 1400 to 1600 ° C., formed into a plate shape, and then cooled to produce a glass substrate, for example, a slot downdraw method, a fusion method, a float method, etc. The glass substrate formed into a plate shape by these methods may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to increase the smoothness.
[0048] The glass substrate may be a commercially available glass plate as it is, or a commercially available thin glass plate may be polished to a desired thickness. Examples of commercially available glass plates include Corning 7059, 1737, and EAGLE2000, Asahi Glass AN100, NH Techno Glass NA-35, Nippon Electric Glass OA-10 and T2X-1, Schott D263 and AF45, Matsunami Glass cover glass and slide glass.
[0049] The laminate of the present invention is excellent in mechanical properties, vibration-damping properties, transparency, and impact resistance.
[0050] In the present invention, mechanical properties such as tensile breaking stress and tensile breaking strain can be evaluated by forming the obtained resin composition into a sheet having a thickness of 1 mm, punching it into a dumbbell test piece shape, and measuring the tensile breaking stress and tensile breaking strain based on the stress / strain curve obtained in accordance with JIS K 7161-2. The tensile breaking stress is preferably 4.0 MPa or more, more preferably 5 MPa or more, and even more preferably 6 MPa or more. The tensile breaking strain is preferably 350% or more, more preferably 400% or more, and even more preferably 500% or more.
[0051] In the present invention, the "vibration damping properties" can be evaluated by forming the obtained resin composition into a sheet having a thickness of 1 mm, and measuring the loss factor of an unconstrained composite beam obtained by the central excitation method based on JIS K 7391. More specifically, the loss factor is a value obtained by the method described in the following examples. The larger the loss factor, the better the vibration damping properties. The loss factor is preferably 0.04 or more, and more preferably 0.05 or more.
[0052] In the present invention, "transparency" refers to transparency to visible light, and the "transparency" can be evaluated by forming the obtained resin composition into a sheet with a thickness of 1 mm, placing the sheet in a spectrophotometer, and measuring the transmittance of visible light with a wavelength of 480 nm. The transmittance is preferably 70% or more, more preferably 73% or more, and even more preferably 75% or more.
[0053] In the present invention, the "impact resistance" can be evaluated by the 50% breaking height determined by the evaluation method described below. The 50% breaking height is preferably 400 mm or more, and more preferably 700 mm or more.
[0054] The laminate of the present invention can be suitably used as a display member or a glass interlayer film for smartphones, tablet PCs, foldable devices, notebook PCs, car navigation systems, in-vehicle displays, digital signage, and the like. EXAMPLES
[0055] The present invention will now be described in detail with reference to examples. The measurement and evaluation methods for each characteristic value in the examples are as follows. (1) Volume percent of spherical silica particles in the resin composition The dispersions obtained in the Examples and Comparative Examples were poured into a 1 mm-thick mold sandwiched between two glass plates with FEP (a copolymer of tetrafluoroethylene and hexafluoropropylene) sheets attached, and heated in an oven at 70°C for 15 hours to obtain a 1 mm-thick sheet of the resin composition. The density of the resin composition (d(g / m)) was measured using a dry density meter (AccPyc1330) manufactured by Shimadzu Corporation. 3 )) and the weight retention rate (%) obtained from the weight (m(g)) residual after heating at 500°C for 1 hour measured using a Shimadzu Corporation differential thermal and thermogravimetry simultaneous analyzer (DTG-60) was used to calculate the volume percent (V(%)) of the spherical silica particles according to the following formula. V(%)=[density of resin composition (g / cm 3 )] × [Weight retention after heating at 500°C for 1 hour (%)] ÷ [Density of spherical silica particles (2.2 g / cm 3 )]
[0056] (2) Mechanical properties (tensile breaking stress, tensile breaking strain) From the sheet obtained in (1), a No. 7 dumbbell test piece (JIS K 7161-2) was prepared using a punching die. In accordance with JIS K 7161-2, a tensile testing machine (EZ-LX) manufactured by Shimadzu Corporation was used to obtain stress / strain curves and measure the tensile stress at break and the tensile strain at break under standard conditions (temperature 23±2°C, in air, humidity (50±10%)) at a tensile speed of 0.1 mm / min up to a strain of 0.3% and at a tensile speed of 50 mm / min beyond the strain of 0.3%. (2-1) Tensile breaking stress The tensile breaking stress was evaluated according to the following criteria. 〇: 4.0MPa or less tensile breaking stress ×: Tensile breaking stress < 4.0MPa (2-2) Tensile breaking strain The tensile breaking strain was evaluated according to the following criteria. 〇: 400% or less tensile breaking strain ×: Tensile breaking strain <400%
[0057] (3) Vibration damping characteristics (loss factor) The resin composition sheet obtained in (1) with a thickness of approximately 1 mm was cut into a 10 mm x 250 mm test piece, and adhered to a 1 mm thick substrate (SPCC material) with an adhesive (manufactured by Toagosei Co., Ltd., product name: Aron Alpha (registered trademark, jelly-like)) to prepare a non-constrained composite beam. The loss factors of the unconstrained composite beams obtained were measured at the second to seventh anti-resonance points in the frequency range of 1 to 6 kHz using a loss factor measurement device (manufactured by Brüel & Kjær) with a measurement temperature range of -20 to 40°C using the central excitation method (JIS K 7391). The vibration damping properties were evaluated by comparing the maximum loss factor values obtained in the above measurement temperature range. Note that the larger the loss factor, the higher the vibration damping properties. ○: Loss factor ≧ 0.04 ×:0.04>Loss factor
[0058] (4) Transparency (parallel light transmittance at 480 nm) The 1 mm-thick sheet of the resin composition obtained in (1) was subjected to a UV-Vis-Infrared Spectrophotometer V-670 (manufactured by JASCO Corporation) to measure the parallel light transmittance at a wavelength of 480 nm, which corresponds to blue visible light, and evaluated according to the following criteria. ○: Parallel light transmittance at 480 nm ≧70% ×: 70%> Parallel light transmittance at 480 nm
[0059] (5) Impact resistance (50% breaking height) The laminate (50 mm long x 50 mm wide) was placed with the glass substrate side facing up, and a stainless steel plate (1.5 mm thick, SUS304, manufactured by Nippon Test Panel Co., Ltd.) was placed under the resin layer. A steel ball weighing 225.6 g and measuring 38.1 mm in diameter was dropped onto the glass substrate side from various drop heights, and the height at which 10 samples either broke or did not break (standard drop height H) was determined. Based on the DuPont impact strength measurement method of JIS K 5400, a steel ball was dropped from a standard drop height H to determine whether or not the glass substrate was broken. If breakage was observed in the glass substrate, the drop height of the steel ball was lowered by one level and the test was conducted again. If breakage was not observed in the glass substrate, the drop height of the steel ball was increased by one level and the test was conducted again. The drop test was repeated a total of 20 times, and the 50% breakage height (H50) was calculated using the following formula. The change interval d for each level was 50 mm. H 50 =H+d(Σ(i-ni) / N-1 / 2) H = Standard drop height (mm) d = Height change interval (mm) i = number of levels (...3, 2, 1, 0, -1, -2, -3...) ni = number of times failure occurred at each level N = total number of times destruction occurred (=Σni) The impact resistance of the laminate was evaluated by comparing the 50% breaking height obtained under the above conditions. ○: 50% breaking height ≧ 300mm ×:300mm>50% breaking height
[0060] Example 1 2712 parts by mass of diethylene glycol monomethyl ether methacrylate (MEO2MA, manufactured by Aldrich Co.) and 3288 parts by mass of spherical silica particles having an average particle size of 110 nm (Silbol110, manufactured by Fuji Chemical Co., Ltd.) were placed in a test tube and dispersed at 5°C for 10 minutes using an ultrasonic homogenizer (UP200St, manufactured by Hielscher Co., Ltd.). Next, 3.55 parts by mass of 2,2'-azobisisobutyronitrile (manufactured by Kanto Chemical Co., Ltd.) was added as a polymerization initiator and mixed to obtain a dispersion liquid. The obtained dispersion was applied to a glass substrate (OA-10G, manufactured by Nippon Electric Glass Co., Ltd., size 50 mm × 50 mm, thickness 0.05 mm) so that the thickness after polymerization would be 100 μm. A PET film (Emblet S-50, manufactured by Unitika Ltd.) was attached as a protective film, and the substrate was heated in an oven at 70°C for 15 hours. The PET film was then peeled off to obtain a laminate.
[0061] Comparative Examples 1 to 3 A laminate was obtained in the same manner as in Example 1, except that the filling amount of the silica particles was changed to that shown in Table 1.
[0062] Table 1 shows the evaluation results of the resin compositions obtained in the examples and comparative examples and the laminates produced using them.
[0063] [Table 1]
[0064] The laminate of Example 1 had excellent mechanical properties, with a large tensile stress at break and a large tensile strain at break, a high parallel light transmittance and excellent transparency, a large loss factor and excellent vibration damping properties, and a high 50% breaking height and excellent impact resistance.
[0065] The laminate of Comparative Example 1 did not contain silica particles, and therefore had poor mechanical properties, such as small tensile breaking stress and tensile breaking strain, and poor vibration damping properties, such as a low loss factor. In addition, the 50% breaking height was low, and the impact resistance was poor.
[0066] The laminate of Comparative Example 2 had a small filling amount of silica particles, and therefore had a small tensile breaking stress, a low parallel light transmittance, and poor transparency, and therefore the loss factor and 50% breaking height were not evaluated.
[0067] In Comparative Example 3, when dispersing the silica particles in the acrylate monomer (A), the dispersion liquid became highly viscous, making dispersion difficult, and therefore a resin composition could not be obtained.
Claims
1. A laminate in which a resin composition containing a polyacrylate resin and silica particles is laminated on at least one surface of a transparent substrate, The polyacrylate resin comprises at least The following general formula (1): 【Chemistry 1】 [In formula (1), R 0 represents a hydrogen atom, a methyl group, or an ethyl group; R 1 represents a hydrogen atom or a methyl group; and n represents an integer of 1 to 9.] as a monomer unit, The content of the silica particles is 15 to 50 volume % of the total volume of the resin composition, The silica particles have an average particle size of less than 150 nm.
2. R 0 The laminate according to claim 1 , wherein is a methyl group.
3. 3. The laminate according to claim 1, wherein the resin composition has a tensile breaking stress of 4.0 MPa or more.
4. 3. The laminate according to claim 1, wherein the resin composition has a tensile breaking strain of 350% or more.
5. 3. The laminate according to claim 1 or 2, wherein a loss factor of an unconstrained composite beam determined by a central excitation method based on JIS K 7391 using a 1 mm thick sheet made of the resin composition is 0.040 or more.
6. 3. The laminate according to claim 1, wherein the transmittance of visible light having a wavelength of 480 nm is measured using a sheet having a thickness of 1 mm made of the resin composition, and the transmittance is 70% or more.
7. 3. The laminate according to claim 1, wherein the 50% breaking height of the laminate is 300 mm or more.
Citation Information
Patent Citations
Vibration-damping polyester resin composition
JP2008189854A
Glass panel and picture display unit
JP2015093401A
Cited By
UV shielding agent and method for producing the same
JP7870584B1
Ultraviolet blocking agent and method for producing same
WO2026181405A1